Introduction of Carbon Substituents into Nitroarenes via Nucleophilic Substitution of Hydrogen: New Developments - Loska, Rafał; Mąkosza, Mieczysław (Synthesis, 2020)
Nucleophilic substitution of hydrogen in nitroarenes has become a powerful synthetic tool for functionalization of these important organic substrates, complementary to other modern methods. In this review we present new developments in the area of introduction of alkyl and functionalized alkyl substituents into nitroarene rings via nucleophilic substitution of hydrogen, followed by application of these processes in the construction of carbo- and heterocyclic rings. Finally, new developments in the investigation of the mechanism of SNArH are summarized.1 Introduction2 Alkylation and Haloalkylation3 Functionalized Carbon Substituents4 Formation of Carbo- and Heterocyclic Rings5 Mechanistic Aspects of SNArH6 Conclusion
Keywords: nucleophilic substitution; aromatic substitution; nitroarenes; carbanions; alkylation